EVALUATION OF BENGKULU CITY REGIONAL REGULATION NO. 11 OF 2021 CONCERNING THE IMPLEMENTATION OF CHILD-FRIENDLY CITIES - Daniska Ossa Amanda; Bobby Mandala Putra; Edi Darmawi (Indonesian Journal of Social Sciences, Policy and Politics, 2024)
Based on Regional Regulation no. 11 of 2021 Bengkulu City concerning the implementation of a Child Friendly City. KLA is a city with a development system that guarantees the fulfillment of children's rights and special protection for children in a planned, comprehensive and sustainable manner. This research aims to determine the evaluation of the regional regulatory policy process focusing on article 8 Number 3 regarding the fulfillment of family environmental rights and alternative care for children. The research method uses qualitative. The results of the research show that in the evaluation of Regional Regulation Number 11 of 2021 of Bengkulu City concerning Child Friendly Cities regarding Article 8 Number 3 concerning the fulfillment of family environmental rights and alternative care, that the City Government has provided facilities for every fulfillment of child care. It can be concluded that: 1) The city government has fulfilled its provision of facilities, whether in the form of complaints or assistance. 2) There is still a lack of a routine agenda and a lack of comprehensive socialization programs for the community. The suggestion is to improve and develop the program agenda as a whole in the form of comprehensive outreach to the community regarding children's rights in order to seek understanding and public awareness regarding the protection and rights of children.